BISAKAH AKU PAKAI INI KE HANGOUT? KETIKA SEPATU BASKET MELANGKAH KE DUNIA KASUAL - Muhamad Amar Ma’ruf; Agatha Dinarah Sri Rumestri; Laurensius Windy Octanio Haryanto (eProceedings of Art & Design, 2025)
High cut basketball shoes are known for their superiority in providingoptimal stability for the user's feet. However, this safety feature often sacrificesflexibility of movement, which is a challenge for athletes. This problem is increasinglyrelevant with the finding that teenage male basketball athletes use basketball shoesnot only for sports needs, but also as a means of expressing themselves in the socialsphere known as athleisure. This phenomenon gives rise to the concept of "beauty ispain" in the male version, where they are willing to sacrifice comfort for appearance.To answer this need, high cut basketball shoes using design thinking method withadjustable collars were developed as a solution with a styling approach using brandarchetypes, namely The Ruler and outlaw archetypes, which then gave birth to theProject Monarch series and the Project Exile series. Keywords: athleisure, high cut, The Ruler, The Outlaw, brand archetype